The dependence of tokamak L-mode confinement on magnetic field and plasma size, from a magnetic field scan experiment at ASDEX Upgrade to full-radius integrated modelling and fusion reactor predictions. (20th March 2023) - Angioni, C.; Bonanomi, N.; Fable, E.; Schneider, P.A.; Tardini, G.; Luda, T.; Staebler, G.M.; ,
Abstract: The dependence of the confinement of a tokamak plasma in L-mode on the magnetic field is explored with a set of dedicated experiments in ASDEX Upgrade and with a theory-based full-radius modelling approach, based on the ASTRA transport code and the TGLF-SAT2 transport model and only using engineering parameters in input, like those adopted in scaling laws for the confinement time. The experimental results confirm the weak dependence of the global confinement on the magnetic field, consistent with the scaling laws for L-mode plasmas and in agreement with the full-radius TGLF-SAT2 predictions. The modelling approach is then extended to numerically investigate the confinement dependence on magnetic field, plasma current and plasma size. The weak dependence of the L-mode confinement on the magnetic field at constant plasma current and plasma size is shown to be produced by a balance between the decrease of confinement mainly produced by the reduction of the E × B shearing rate and the increase of confinement provided by the reduced gyro-Bohm factor, when the magnetic field is increased. The ASTRA/TGLF-SAT2 predicted increase of confinement with increasing plasma size is investigated in comparison with the predictions of the global confinement scaling laws for L-mode plasmas and the Bohm and gyro-Bohm dependencies of confinement, highlighting interesting similarities and important differences. Full-radius TGLF-SAT2 simulations with increasing plasma size are then extended to dimensions which are compatible with reactor relevant fusion power production, using ITER and the European DEMO as references. ASTRA/TGLF-SAT2 predictions of fusion power and confinement of an L-mode fusion reactor are presented at both 5.7 T and 10 T of magnetic field on the magnetic axis.